Structure of finite inverse semigroup with zero, in which every stable order is fundamental or antifundamental - Derech, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We find necessary and sufficient conditions for any stable order on a finite inverse semigroup with zéro to be fondamental or antifundamental.